Follow-up of women with atypical squamous cells cannot exclude high-grade squamous intraepithelial lesions (ASC-H) - López-Alegría, Fanny; Lorenzi, Dino Soares De; Quezada, Orlando Poblete (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: The concept that the presence of atypical squamous cells cannot exclude high-grade squamous intraepithelial lesions (ASC-H) was introduced in the 2001 Bethesda System of cervical cytology classification. This nomenclature defines cervical cancer precursor lesions. The objective of this study was to investigate the colpocytological-histological results from a three-year follow-up conducted on a cohort of women with reports of ASC-H who were attended during 2005-2006 at clinics of the Southern Metropolitan Healthcare Service of Santiago, Chile. DESIGN AND SETTING: Prospective cohort study at primary healthcare clinics in Santiago, Chile. METHODS: Colpocytological-histological follow-up was conducted over a three-year period on 92 women with cytological reports of ASC-H who were attended at primary healthcare clinics during 2005-2006. RESULTS: At the end of the follow-up period, high-grade lesions were evaluated and the following outcomes were observed: seven women presented invasive cancer (7.6%), 49 presented high-grade lesions (53.3%), 26 presented low-grade lesions (28.2%) and 10 presented normal results (10.9%). The “Conditional Probabilities Tree Diagram” was used to show the results from tests and the times of lesion detection. It demonstrated that, after a first report of ASC-H, clinical management needed to be interventionist. CONCLUSION: The follow-up on our cohort of women showed that the majority of uncertain ASC-H diagnoses (82.6%) had abnormal colposcopic results and that during the follow-up using ASC-H smears, two out of every three women developed high-grade lesions.